Failure modes and effects analysis for an engineering design modification in the US nuclear power industry. (25th March 2019) - Torres-Jiménez, Pamela M.
Engineering design modifications for nuclear power plants can be extensive and complex projects involving numerous activities and multi-discipline resources. Failure modes, or risks, involved with these activities can impact project cost, schedule, or even introduce safety hazards. The identification of risks and the establishment of detection and mitigation strategies early on the project development stage can prevent future adverse effects on project cost and schedule. This paper focuses on the evaluation of risks that can arise during the development of a conceptual design modification project at a US nuclear power plant using the failure modes and effects analysis tool. The analysis evaluates a list of activities to be completed as part of a conceptual design package. Failure modes are identified for each activity and ranked for severity, the likelihood of failure, and opportunity for detection. These ranks are later used to calculate a risk priority number for each activity. This number is used to identify the activities with higher risk to assist engineers in the development of person-hour estimates for projects. The results presented in this paper are expected to support the US nuclear industry in the identification and mitigation of risks beyond what is already addressed in plant-specific procedures.